Sustained clinical response and safety of etanercept in patients with early axial spondyloarthritis: 10-year results of the ESTHER trial. (January 2021) - Proft, Fabian; Weiß, Anja; Torgutalp, Murat; Protopopov, Mikhail; Rodriguez, Valeria Rios; Haibel, Hildrun; Behmer, Olaf; Sieper, Joachim; Poddubnyy, Denis
Aims: Long-term data on TNFi treatment in patients with axSpA is scarce. The objective of this analysis was to assess long-term clinical efficacy of etanercept in early axSpA [including both non-radiographic and radiographic axSpA forms], who participated in the long-term (until year 10) extension of the ESTHER-trial. Methods: In the previously reported ESTHER-trial, patients with early active axSpA were randomized to treatment with etanercept ( n  = 40) or sulfasalazine ( n  = 36) during the first year. Patients in remission discontinued their therapy and were followed up until the end of year 2; in case of remission-loss, etanercept was (re)-introduced and continued until the end of year 10. If remission was not achieved at year 1, patients continued receiving (or were switched to) etanercept for up to 10 years. Results: A total of 19 patients (12 with r-axSpA and 7 with nr-axSpA at baseline) out of the initial 76 patients (= 25%) completed year 10 of the study. In the entire group, a sustained clinical response was seen over 10 years of follow up in the as-observed analysis. Completers were significantly more often male and showed lower values of patient and physician global assessments of disease activity, Ankylosing Spondylitis Disease Activity Score (ASDAS), and Ankylosing Spondylitis Quality of Life questionnaire (ASQoL) scores at baseline as compared with non-completers. When analyzing clinical data of the completers, mean Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) values were constantly below 2 and mean ASDAS below 2.1 during follow up with no statistically significant differences between the r-axSpA and nr-axSpA subgroups. A total of 39 serious adverse events were documented over the 10 years, while six of them were seen as possibly associated with the etanercept treatment, which led in five patients to treatment discontinuation. Conclusion: A sustained clinical response was observed over the 10 years of the study with comparable response and drop-out rates between r-axSpA and nr-axSpA. Etanercept was well tolerated across the entire treatment period and showed a good safety profile with no new safety signals.